2018
DOI: 10.1002/jpln.201700470
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transgenicBtrice and its non‐Btcounterpart in adaptability to nitrogen deficiency

Abstract: Resistances of newly bred Bacillus thuringiensis (Bt) crops have been dramatically improved because of the effective and high expression of Bt protein in the plant. However, poorer adaptabilities to environmental stresses were observed in some Bt crops compared to their non‐Bt counterparts. The biological reasons for the poorer adaptabilities were still unclear. A nitrogen (N) deficiency experiment was conducted to investigate variations in growth and physiology characteristics of a newly bred Bt rice [Oryza s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It also was found that the high Cry1Ca accumulation in plants had strong unintended effects 13 . Compared with the receptor variety, the Bt rice Huahui‐1 showed reduced adaptability to nitrogen deficiency, 45 drought stress 46 and saline‐alkaline stress 47 . Further studies showed that the unintended effects of Huahui‐1 may result from cellular localization 17 and protein interactions of exogenous Bt protein 16 .…”
Section: Discussionmentioning
confidence: 99%
“…It also was found that the high Cry1Ca accumulation in plants had strong unintended effects 13 . Compared with the receptor variety, the Bt rice Huahui‐1 showed reduced adaptability to nitrogen deficiency, 45 drought stress 46 and saline‐alkaline stress 47 . Further studies showed that the unintended effects of Huahui‐1 may result from cellular localization 17 and protein interactions of exogenous Bt protein 16 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that an array of agronomic traits, including tiller number, biomass, and grain weight per plant, were significantly lower in insect-resistant transgenic cry1Ab/c rice Huahui-1 (HH1) than those in the parental line Minghui-63 (MH63) under saline-alkaline stress ( Fu et al, 2018 ). Moreover, HH1 showed reduced adaptability to nitrogen deficiency and drought than that its parental line MH63, which may be related to high Bt protein expression in the transgenic line ( Jiang et al, 2018a , b ). However, the underlying molecular mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 97%